The relationship of work family conflict and job performance at HSE Resources Sdn. Bhd. Paka, Terengganu / Siti Fahirah A Rosli - A Rosli, Siti Fahirah (Faculty of Business Management, 2017)
The purpose of this research is to identify the relationship between work-family conflict and the job performance of the employee at Hse Resomces Sdn. Bhd, Paka Terengganu. The elements in this research are work to family conflict, family to work conflict and cooperative strategy. In order to increase the good job performance of the employee at the work place, the company should motivate and give inspiration to the employee and not downgrade the employee because it could affect the outcome of the job.